Denúncia e Anklageschrift : um estudo contrastivo - Reichmann, Tinka (Language and Law / Linguagem e Direito, 2016)
In this article, we apply a method of analysis of contrastive textology in the legal context, analysing two text genres that have a comparable function in Brazilian and German criminal procedures: “denúncia” and “ Anklageschrift”. The purpose is to bring to light similarities and dierences that help translators to understand the source text and to dene invariance criteria and translation methods and procedures, as well as to write the target text for the other legal culture. At the end, the potential of the research is shown by the prospective broadening of the focus from individual text specimen to textual networks.